Cross-over in the dynamics of polymer confined between two liquids of different viscosity. Issue 3 (6th June 2019) - Giunta, Giuliana; Carbone, Paola
Abstract : Using molecular dynamics simulations, we analysed the polymer dynamics of chains of different molecular weights entrapped at the interface between two immiscible liquids. We showed that on increasing the viscosity of one of the two liquids the dynamic behaviour of the chain changes from a Zimm-like dynamics typical of dilute polymer solutions to a Rouse-like dynamics where hydrodynamic interactions are screened. We observed that when the polymer is in contact with a high viscosity liquid, the number of solvent molecules close to the polymer beads is reduced and ascribed the screening effect to this reduced number of polymer–solvent contacts. For the longest chain simulated, we calculated the distribution of loop length and compared the results with the theoretical distribution developed for solid/liquid interfaces. We showed that the polymer tends to form loops (although flat against the interface) and that the theory works reasonably well also for liquid/liquid interfaces.